Aspects of the safe use of medicinal products based on medicinal plant materials in COVID-19 - A. A. Taube (Реальная клиническая практика: данные и доказательства)
According to a number of studies, medicinal plants and drugs based on them can be used as inhibitors of various viral infections, including the SARS-CoV-2 virus at different stages of their manifestation and development. In a number of countries, official recommendations have been developed for independent and auxiliary therapy of COVID-19 with medicinal plants and drugs based on them. However, in combination with drugs developed for the treatment of COVID-19, various interactions, including adverse ones, may occur.Purpose: to systematize and analyze data on possible interactions of medicinal plants and natural biologically active substances, which are major active substances in plant raw materials, with medicinal products recommended for the treatment of COVID-19.Materials and methods. The study selected drugs recommended for the treatment of COVID-19 at various stages and severity with different mechanisms of action. We used open information on confirmed drug interactions on the website of the international database https://go.drugbank.com/. Results and discussion. The results of possible interactions with the following medicinal plants were revealed: St. John’s wort, Digitalis, Periwinkle, Colchicum, Cinchona, Strophant, Ergot, Pepper, Lemon, Coffee, Tea, Yohimbe tree, Garlic, Evening primrose, Poppy opium, Rauwolfia serpentine.Conclusion. The drugs used for the treatment of COVID-19 of different anatomical and therapeutic groups are considered, possible changes in their therapeutic efficacy are identified when taken simultaneously with medicinal plants or biologically active substances of plant origin contained in food and nutritional supplements. It is shown that not all interactions may be undesirable. The effect of medicinal plants on the pharmacokinetics of drugs has not been studied enough and seems to be an important and promising aspect of pharmacovigilance activities. Interesting interactions have been identified: St. John’s wort and drugs based on it can cause the induction of CYP3A and reduce the therapeutic effect when used together with drugs: lopinavir, remdesivir, umifenovir, nirmatrelvir; the cardiotoxic effect of interferon can be reduced through the use of medicinal plant materials containing cardiac glycosides; the combination of ferulic acid with peginterferon alfa-2a increases the risk and severity of bleeding. It was found that the Drugbank database does not contain information on drug-drug interactions of medicinal plants with molnupiravir.